Relations between Ethnocentrism and National Attachment - Petrović, Danijela S.; Pavićević, Miljana S. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
Belonging and being attached to various social groups, such as nationality and ethnicity, can have a significant motivational effect. At the same time, a sense of national attachment can develop into ethnocentrism and become a source of hostility and conflicts among members of different nations, with conflicts in the immediate past contributing to greater manifestations of certain forms of national attachment, and even ethnocentrism. That is why the objectives of this paper were to: (1) determine prominence of ethnocentrism and different forms of national attachment in young people of Serbian nationality in Kosovo and Metohija (345 respondents, average age AS=19,36) (2) investigate what kind of relationship exists between ethnocentrism and national attachment. Instruments used in the research were the Ethnocentrism Scale (Šram, 2010) and Scale of National Attachment Forms (Rot and Havelka, 1973). The results show that of all aspects of ethnocentrism, respondents manifest the greatest degree of national homogenization, distinguished by a strong need for national unity, while the most accentuated form of national attachment is prominent national attachment, characterized by idealizing one’s own nation and emphasizing the feeling of patriotism. Prominent and exclusive forms of national attachment correlate with all the aspects of ethnocentrism which supports the claim that those individuals who are characterized by a high degree of national idealization, which is a feature of both prominent and exclusive national attachment, often demonstrate a certain tendency to react in an ethnocentric way.
Keywords: adolescents; national attachment; ethnocentrism